Inovasi Model Pembiayaan Musyarakah untuk Optimalisasi Modal Kerja : Studi pada BMT Dana Barokah Muntilan - Widiyawati, Ema Nurkholisa; Fitriyani, Yeny; Purwanto (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Musyarakah financing plays a significant role in supporting micro-enterprise development at BMT Dana Barokah Muntilan; however, its contribution remains limited, requiring innovation to achieve greater effectiveness. This study aims to examine the implementation of innovative musyarakah financing models to optimize working capital and to identify the challenges encountered in practice. A qualitative case study approach was employed by collecting data through interviews, observations, and documentation involving BMT managers and members. The findings reveal innovations such as the integration of musyarakah and ijarah contracts, the application of transparent profit-sharing schemes, the use of wadiah accounts for disbursement mechanisms, and continuous business monitoring by Account Officers. These innovations have been shown to enhance members’ responsibility, strengthen financial literacy, and ensure business sustainability. The study concludes that the innovative musyarakah model can effectively optimize working capital, although its application is still constrained by limited human resources and the low level of public literacy regarding Islamic contracts.